PENCEMARAN LOGAM BERAT MERKURI (Hg) PADA AIRTANAH - Thomas Triadi Putranto (Diponegoro University, 2011)
The earth consists largely of water because the land area is smaller than the ocean. Human beings on this earthcan not escape the need for water. Water is the main requirement for the process of life on the earth.Relatively clean water that is coveted by men, whether for purposes of daily life, for industrial purposes, for thecleanliness of city sanitation, as well as for agricultural purposes and so forth. Heavy metal pollution is a veryserious issue to be handled, because of adverse environmental and ecosystem in general. Heavy metallic elementis the element which has a density of more than 5 gr/cm3. Hg has a density of 13.55 gr/cm3. Disaster is anoutbreak of Minamata mercury poisoning in people who eat fish contaminated by mercury in Minamata Japan,and this event is known as Minamata Disease. Efforts to tackle the heavy metal pollution can actually be doneusing a chemical process or by microorganism such as microbes and bacteria.